Hippocampal Necrosis in a Cat from Australia - Carl Adagra; Susan Amanda Piripi (Case Reports in Veterinary Medicine)
This paper reports findings from a feline case of hippocampal necrosis. A seven-year-old neutered female cat was seen with a history of behavioural change followed by complex focal seizures. The cat was severely pyrexic on presentation and anisocoria was present. It was treated with cooling, intravenous fluid, and phenobarbitone administration which was later changed to levetiracetam. An MRI was performed and revealed findings of a hypointense T1 and hyperintense T2 signal in the hippocampus and inferior temporal gyrus with mild gadolinium uptake, findings which were consistent with previous cases of hippocampal necrosis. The cat was witnessed to vomit and aspirate 24 hours after diagnosis leading to cardiac arrest and death. Postmortem examination revealed a subacute degenerative encephalopathy involving the hippocampus.